A DAPATKAH KETIMPANGAN HUKUM YANG TERDAPAT DI DALAM KASUS “ICE COLD” MENJADI SEBUAH AMUNISI KUAT UNTUK MENGAJUKAN PK KE - 2 ? : DAPATKAH KETIMPANGAN HUKUM YANG TERDAPAT DI DALAM KASUS “ICE COLD” MENJADI SEBUAH AMUNISI KUAT UNTUK MENGAJUKAN PK KE - 2 ? - Wiguno, Ahadira Setyo (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
The murder case of Mirna by the defendant Jessica caused a lot of controversy, especially after the publication of the documentary entitled "Ice Cold" which contained a series of "cyanide" cases from the beginning to the end of the verdict handed down to the murder suspect Jessica Kumala Wongso. The purpose of this research is to show the irregularities in this case and provide the author's argument regarding the sentence and decision of the presiding judge and JPU (Public Prosecutor) which raises many questions due to the lack of valid evidence such as violations of principles in the process. trials regulated in the KUHAP Book. The research method used in this article is the Normative Juridical method with a Qualitative analysis approach and a Literature Study approach. The formulation of the problem in this research is, what are the parameters and conditions for submitting a 2nd Judicial Review, if in Jessica's case she wants to carry out a 2nd Judicial Review. The results of the research are that Jessica and the defendant's legal team must carry out an examination and review the evidence of irregularities regarding the case “Ice Cold” which started appearing recently. This must be done to fulfill the requirements for submitting the 2nd Judicial Review which contains the following, if the judge's decision in the trial contains lies, false evidence that incriminates one of the parties, both the plaintiff and the defendant, then there are documents of evidence that are decisive, then there is a judge's decision granting something that is not demanded or more than what is demanded, there is a part regarding a claim in the lawsuit that has not been decided without any consideration of the reasons, there are conflicting decisions, even though the parties are the same, regarding the basis or issue in question. the same, or at the same level. Keywords: Murder; Documentaries; 2nd Judicial Review.